Management of Packet Queues in Buffer using Proactive Protocol (International Journal of Engineering and Computer Science, 2015)
Mobile Ad hoc Network is a self-configuring infrastructure less wireless network in which nodes are mobile in nature and they form a temporary network. Each mobile node is free to move anywhere independently in any direction. As the number of nodes in the network increases the transfer of packets also increases so it becomes necessary to give priority to the packets. When packets are processed according to their priority then more packet or same service may arrive at processing node and hence it becomes necessary to queue the incoming packets in the buffer. Thus the primary objective of the research work is on management of buffer space for queuing the packets. Active queue management scheme is used for queuing packet in which sending node is notified before the queue is about to filled completely so sender can stop sending data or lower the rate of data transmission. The MANET model which is considered is working on Optimized Link State routing protocol (OLSR). In this paper, the performance of the protocol is analyzed and compared with previous work on the basis of parameters Delay and Throughput. After the evaluation and comparison of results, it is concluded that the performance of OLSR is better than AODV protocol.